Role of technology entrepreneurship in the development of innovativeness of small and medium-sized enterprises - Matejun Marek (Management)
Technology entrepreneurship is an interesting concept for transforming the potential of the scientific and research and development fields (including a wider impact of the so-called business environment sphere) into innovative products and services. In consequence, it might become a key factor in building the innovation potential of modern enterprises, especially SME sector enterprises, which due to their resource shortages have limited ability to carry out independent research and development operations. Taking the above into account, the aim of the article is to identify and evaluate the role of entrepreneurship in the development of innovativeness of SMEs. To achieve this aim, a survey was conducted on a sample of 300 SMEs based in ithe łódzkie province.